Contribution of a Geographic Information System to Assess the Vulnerability to Groundwater Pollution of the Free Water Table from the Oued Souf Region (South-East Algeria) - Khelfaoui, Faycal; Sayad, Lamine; Attoui, Badra; Bouselsal, Bouualem; Ghezaili, Salah (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Oued Souf free aquifer located in the South East of Algeria represents the main water resource used mostly for urban and agricultural activities. The intensive use of chemical fertilizers has led to serious environmental problems such as contamination of the free aquifer in the region. Thus, aquifer vulnerability has been assessed using several different methods (DRASTIC, GOD, and the Susceptibility Index "SI") based on a geographic information system (GIS).
Keywords: free aquifer; Oued Souf; chemical fertilizer; vulnerability; DRASTIC; GOD; susceptibility index; pollution; SIG; warstwa wodonośna; nawozy chemiczne; zanieczyszczenia